An Efficient High Gain DC-DC Converter for Automotive Applications - Aiswarya T.M.; M. Prabhakar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents a high gain DC-DC converter which uses a clamp circuit to achieve soft switching. The proposed converter is designed to supply a high intensity discharge (HID) lamp used in automobile head lamps. The converter operates from a 12V input supply and provides an output voltage of 120V at 35W output power. A clamp circuit consisting of a clamp capacitor, clamp switch and resonant inductor will help to achieve zero voltage switching (ZVS) of the both main and clamp switches. The practical performance of the converter was validated through experimental results. Results obtained from the prototype hardware prove that the converter meets the requirements of HID lamp application and can be a very good alternative to existing converters.